Photoprotection Practice and Skin Health Habits on the Incidence of Pigmentation - Ferra Olivia Mawu; Paulus Mario Christopher; Marlyn Grace Kapantow; Maryam Sun Dunggio (Jurnal Kesehatan Masyarakat, 2026)
The skin is susceptible to intrinsic and extrinsic factors — including sun exposure, diet, and lifestyle which can disrupt homeostasis and induce pigmentation. This pilot study evaluated photoprotective behaviors and skin health habits and their association with pigmentation incidence among medical students at Sam Ratulangi University, Indonesia (February–April 2024). Using a self-administered questionnaire, 94 valid respondents were included (mean age 21.4 ± 1.7 years; response rate 37.6%). Pigmentation was reported by 34.0% of respondents, predominantly female (59.8%). Associated factors included irregular sunscreen use, history of sunburn, passive smoking, prolonged sun exposure, poor dietary habits, insufficient sleep, limited exercise, and elevated stress. Statistically significant associations (P < 0.05) were identified for daily sunscreen use, sunscreen use during outdoor activities, history of sunburn, and daily stress. Although pigmentation incidence was relatively low, concerning gaps in photoprotective and skin health behaviors were observed. As future healthcare providers, medical students represent a critical target population. Early education on sun-related damage, photoprotection, and skin health habits is recommended to improve knowledge, attitudes, and practices in this group.